2014
DOI: 10.3390/ijms15058063
|View full text |Cite
|
Sign up to set email alerts
|

CB2 Receptor Activation Inhibits Melanoma Cell Transmigration through the Blood-Brain Barrier

Abstract: During parenchymal brain metastasis formation tumor cells need to migrate through cerebral endothelial cells, which form the morphological basis of the blood-brain barrier (BBB). The mechanisms of extravasation of tumor cells are highly uncharacterized, but in some aspects recapitulate the diapedesis of leukocytes. Extravasation of leukocytes through the BBB is decreased by the activation of type 2 cannabinoid receptors (CB2); therefore, in the present study we sought to investigate the role of CB2 receptors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…Immune cells preponderantly express CB 2 . Consistent with this observation, there is a large body of data that supports a functional relevance for 2-AG as acting through CB 2 to inhibit migratory activities for a diverse array of immune cell types [74, 75]. Indeed, it has been suggested that 2-AG is the cognate functionally relevant eCB for CB 2 .…”
Section: Immune Systemmentioning
confidence: 71%
“…Immune cells preponderantly express CB 2 . Consistent with this observation, there is a large body of data that supports a functional relevance for 2-AG as acting through CB 2 to inhibit migratory activities for a diverse array of immune cell types [74, 75]. Indeed, it has been suggested that 2-AG is the cognate functionally relevant eCB for CB 2 .…”
Section: Immune Systemmentioning
confidence: 71%
“…Activation of CB1 and CB2 regulates cell migration and cytokine and chemokine production, with CB2 activation by 2-AG inhibiting migratory activities of immune cells [183,184]. AEA also inhibits production of proinflammatory cytokines, so that it reduces human monocyte interleukin (IL)-6 and IL-8 [185]; and IL-2, TNF-α and interferon (IFN)-γ from activated human T lymphocytes [186].…”
Section: Ecs and Immunoinflammatory System Dysregulationmentioning
confidence: 99%
“…Brain is considered a privileged site for the presence of blood brain barrier (BBB) protecting it against the entry of toxic substances and microorganisms [ 12 , 13 ]. Since the CNS also lacks the lymphatic system, the only way of metastatic cells to reach the brain is to cross this barrier [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%